DETERMINING THE METAPHORICAL PERCEPTIONS OF THE FOREIGNERS LEARNING TURKISH REGARDING TURKISH AND TURKISH CULTURE - Altuntaş Gürsoy, İlke (International Online Journal of Education and Teaching, 2022)
In this research, it was aimed to determine learners’ perceptions of the target language and target culture through metaphors. It is structured with a phenomenology design, one of the qualitative research designs. The participants of the study were selected by purposive sampling method. The participants of the research consisted of 101 learners studying Turkish at A2, B1, B2 levels at Ankara Ankara Hacı Bayram Veli University Language Teaching Application and Research Center and Gazi University Turkish Language Learning Research and Application Center which are located in Turkiye. The data were analyzed by content analysis. As a result of the analyses, it was concluded that the learner perceptions regarding Turkish culture were completely positive and 7 learners had negative perceptions regarding Turkish. The frequency of metaphors produced by learners about Turkish is grouped from the highest to the lowest under 6 different categories as interlingual relationship, valuing/positive emotion, difficulty/easiness, need/necessity, individual experience and feature/systematicity. The metaphors they produce about Turkish culture were also grouped under 6 different categories from the highest frequency to the lowest as intercultural relationship, richness/diversity, valuing/positive emotion, always existing/being rooted, individual experience and universality.